Alzheimer's disease : recent findings in pathophysiology, diagnostic and therapeutic modalities - Govindaraju, Thimmaiah (Cambridge, UK : Royal Society of Chemistry, 2022)
Handbook on Alzheimer's disease from aetiology and neurochemistry to diagnostic and therapeutic approaches. Intended to provide an introduction to all aspects of the disease.
2.3.2 When Amyloid Plaque Dysfunctions Together With Tau Pathology That Results in Havoc -- 2.3.3 Other Cellular Mishaps That Converge in the Anomaly of Homeostasis -- 2.4 Genetics as a Promising Tool for Alzheimer's Disease -- References -- Chapter 3 Alzheimer's Disease Pathology: A Tau Perspective -- 3.1 Tau and Alzheimer's Disease -- 3.1.1 Alzheimer's Disease -- 3.2 Conclusions -- 3.3 Future Perspectives for Small Molecules As Tau Therapeutics -- References
Includes bibliographical references and index.
Online resource; title from title screen (Ebook Central, viewed December 13, 2022]).
eBooks on EBSCOhost
Keywords: Alzheimer's disease; Alzheimer Disease; Maladie d'Alzheimer.; Alzheimer's disease